2016
DOI: 10.1186/s13071-016-1909-3
|View full text |Cite
|
Sign up to set email alerts
|

Exon-intron structure and sequence variation of the calreticulin gene among Rhipicephalus sanguineus group ticks

Abstract: BackgroundCalreticulin proteins (CRTs) are important components of tick saliva, which is involved in the blood meal success, pathogen transmission and host allergic responses. The characterization of the genes encoding for salivary proteins, such as CRTs, is pivotal to understand the mechanisms of tick-host interaction during blood meal and to develop tick control strategies based on their inhibition. In hard ticks, crt genes were shown to have only one intron with conserved position among species. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Indeed, oral immunization with TsCalr results in 37% reduction in worm burden and delayed development in a taenisosis experimental model. In addition, TsCalr is expressed in the tegumentary and muscle cytons, neutralization by specific anti-TsCalr IgA could interfere with nutrition across the tegument ( 17 , 57 ). In T. solium organs involved in infection, such as the suckers, showed upregulation of Calr.…”
Section: Differential Expression Of Calreticulinmentioning
confidence: 99%
“…Indeed, oral immunization with TsCalr results in 37% reduction in worm burden and delayed development in a taenisosis experimental model. In addition, TsCalr is expressed in the tegumentary and muscle cytons, neutralization by specific anti-TsCalr IgA could interfere with nutrition across the tegument ( 17 , 57 ). In T. solium organs involved in infection, such as the suckers, showed upregulation of Calr.…”
Section: Differential Expression Of Calreticulinmentioning
confidence: 99%
“…As far as phlebotomine sand flies, in a recent study, the authors were unable to distinguish Evandromyia carmelinoi (Ryan, Fraiha, Lainson & Shaw), Evandromyia evandroi (Costa Lima & Antunes) and Evandromyia lenti (Mangabeira) using cox 1, even considering their clear morphological differences (Rodrigues et al ., 2020). In fact, evolutionary phenomena such as introgression, paternal leakage, heteroplasmy, retention of ancestral polymorphism and/or low interspecific divergence (Rees et al ., 2003; Laurito et al ., 2013; Pinto et al ., 2015; Porretta et al ., 2016; Rodrigues et al ., 2018; Mastrantonio et al ., 2019), should be considered when using DNA‐based approaches.…”
Section: Detecting Cryptic Speciesmentioning
confidence: 99%
“…Szcześniak et al, 2011), ongoing presence/absence polymorphism has never been observed in sponges and only rarely been detected in other groups. To our knowledge, it has only been described in a relatively small number of cases including a Drosophila species (Llopart et al, 2002), Daphnia pulex (Omilian et al, 2008), in a group of closely related Mycosphaerella species (Torriani et al, 2011), and in the tick Rhipicephalus sanguineus (Porretta et al, 2016). Given the rarity of such case studies, each one represents a valuable opportunity to increase our understanding of the evolutionary processes that lead to intron gains and losses in genomes and explain the enormous variation in intron number across eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 18 Only a few examples of intron presence/absence polymorphism within a species are known to date (Llopart et al, 2002;Omilian et al, 2008;Torriani et al, 2011;Porretta et al, 2016). The rarity of such examples with intron degradation, different reading frames along with its geographical distribution indicates that P. robusta potentially represents a valuable opportunity to investigate the mechanisms underlying the spread of an intron through a species.…”
Section: Intron Presence/absence Polymorphismmentioning
confidence: 99%